Diagnóstico da otite média em cães: comparação entre radiografia convencional, canalografia e audiometria de impedância - Leite, C. A. L. (2011)
Radiography (conventional and contrasted - canalography) and audioelectrophysiologic (impedance audiometry) tests were correlated with otitis media in 12 middle ear affected and 12 healthy dogs. When comparing both diagnostic methods, it was found that the reliability in the detection of otitis media in dogs was 100% for the first and 58.3-60.0% for the latter. Thus, it was possible to attest that the impedance audiometry was the most accurate method in the identification of otitis media in dogs when compared with radiographic assessments.